KAJIAN FILOSOFIS LAGU VELOCITY MELALUI TAFSIR AL-‘ASHR DALAM KONTEKS PENDIDIKAN ISLAM - Nashrul Mu'minin (Lembaga Riset dan Inovasi Kreyat Center, 2025)
This study aims to philosophically examine the meaning of time and motion in the song Velocity by Richard Harvey and John Lenehan with a thematic interpretation approach to the Al-'Ashr verse (QS. 103), and evaluate its relevance in the context of Islamic Religious Education (PAI) learning. The song Velocity, although instrumental and without verbal lyrics, represents the dynamics of acceleration that reflect the conditions of modern life that are fast-paced, competitive, and demand awareness of the value of time. Surah Al-'Ashr itself emphasizes the importance of time as a key element of human success, where Allah swears by time to affirm that humans are at a loss except for those who believe, do good deeds, advise each other in truth and patience. The method used in this study is a qualitative method with an approach to Islamic educational philosophy and hermeneutic analysis. The analysis was carried out by examining the musical structure of the song Velocity to identify elements of philosophical representation such as tempo (speed), dynamics, tone progression, and the emotions aroused. Then, these elements are interpreted and associated with the Qur'anic messages in Surah Al-'Ashr through the approach of classical and contemporary thematic interpretation (tafsir al-maudhū'i), which deepens the existential meaning of time in Islamic teachings. The results of the study show that the song Velocity contains a musical structure that aesthetically forms a philosophical narrative about the speed of life, the limitations of time, and the need for self-reflection. The fast tempo and intense tone progression symbolize the dynamics of human life that continues to move towards a certain goal. This is in line with the message of Al-'Ashr which emphasizes the urgency of using time productively and meaningfully. This song can be a reflective medium in Islamic education to build students' awareness of the importance of time, good deeds, and social collaboration in the context of humanistic and contextual Islamic Religious Education learning. Evaluation of the application of the study results in learning shows that an interdisciplinary approach that combines music, philosophy, and Qur'anic interpretation is able to provide a deeper and more applicable understanding for students. The song Velocity can be used as a stimulative media for introducing discussions about time, charity, and Islamic ethics in Islamic Religious Education classes. The conclusion of this study is that philosophical interpretations of musical works of art such as Velocity, when combined with Qur'anic values, can be an innovative educational tool in enriching reflective, contextual, and meaningful religious learning experiences.